Divergent dietary and defensive adaptations of closely related coexisting seed bugs - Nathaniel J. Carlson; Amy P. Hastings; Christophe Duplais; Anurag A. Agrawal (Proceedings of the National Academy of Sciences, 2026)
Ecologists use multiple approaches to decipher factors mediating the origin and maintenance of biodiversity. Using closely related species, we retrospectively investigated divergence in diet and defense among seed bugs that co-occur at small spatial scales. The small milkweed bug ( Lygaeus kalmii ) primarily feeds on milkweeds (Apocynaceae) and sequesters toxic cardenolides as an antipredator defense, both traits representing the ancestral condition of Lygaeinae. Little was previously known about the false milkweed bug ( L. turcicus ); we report that the primary host of L. turcicus is false sunflower, Heliopsis helianthoides (Asteraceae), and that its seeds produce cardenolides, the second report of these toxins in Asteraceae. The dominant cardenolide was novel, which we resolved and named heliopside. We found divergent trends in performance and defense of the two bugs. L . kalmii had >40% higher survival and growth on milkweeds compared to H. helianthoides , an effect that was primarily explained by H. helianthoides’ thick seed shell. Nonetheless, L. kalmii sequestered toxins equivalently from the two seed species. Conversely, L. turcicus had equally high survival and growth on the two seeds, but sequestered toxins more effectively from H. helianthoides than milkweed, potentially due to specialized detoxification of H. helianthoides’ cardenolides. Thus, adaptation to host-plant traits in these two seed bugs is asymmetric for diet and defense, and distinct constraints are likely to limit the bugs’ host ranges and contribute to coexistence. Shared seed chemistry apparently facilitated host shifts in the Lygaeinae from Apocynaceae to Asteraceae, with divergent adaptation to their food niches likely facilitating coexistence.